STUDI TINJAUAN KELAYAKAN EMBUNG GROJOGAN DESA PLANDAAN KECAMATAN PLANDAAN KABUPATEN JOMBANG - Hartanto, Tomy Dwi; Rispiningati, Rispiningati; Cahya, Evi Nur (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
The need for clean water to support human activities continues to increase due to an increasing in population and irrigation needs. Dams and small dam can be an alternative for water management to correct water in the rainy season and being in the dry season. The purpose of Grojogan’s small dam construction is for irrigation of paddy fields in Plandaan sub-district. The greater the water corrected from small dam, the greater its contribution to the profitability of the agricultural system so as to know the magnitude of the carrying capacity of the small dam on the agricultural cropping pattern in the irrigation area. The purpose of this research is to know the magnitude of bearing capacity of small dam on agricultural cropping pattern both economically, socially, and environment. The method used is descriptive analytics. Data are collectied by interview, observation and documentation study. In this research of initial feasibility studies, water balance, and economic analysis. The result of the research shows that the water balance in Grojogan’s small dam is positive, meaning that the water debit that can be accommodated in the small dam is able to supply the irrigation water requirement for 86 Ha, land. The result of economic analysis with usage age for 10-year small dam found the benefit-cost ratio (B / C) ratio = 3.096, while the benefit difference is Rp. 9.858.913.731,21, and the internal rate of return is 36.35%. In the calculation of sensitivity analysis it is found that with the change of values ​​up to 20%, the project is still safe under the value fluctuations.